Identification of Meat Species by Using Molecular and Spectroscopic Techniques - Evrim Güneş Altuntaş; Ebru Deniz; Beycan Ayhan; Kezban Candogan; Duygu Ozel Demiralp (Turkish Journal of Agriculture: Food Science and Technology)
Meat is one of the main nutrition source in the human diet with its excellent protein, vitamin and mineral contents. Despite its advantages, being high-priced makes meat products open to adulteration. Meat products are mixed food types which can contain different species of meat. However, mixing two or more types of meats is not always allowed by laws. On the other hand, replacement high quality meats with cheaper meat types are a cost lowering way for the producers. The commonly consumed meat types differ from country to country, but generally economical, ethnic and religion concerns are in the foreground. In this case, species identification techniques are gaining importance. Although some techniques depending on DNA or spectroscopy have been developed for many years, choosing the best method for species identification is still among the controversial issues today. Thus, the currently used methods and promising techniques in this area were discussed in this review.